2022
DOI: 10.3390/nano12203585
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured MoS2 and WS2 Photoresponses under Gas Stimuli

Abstract: This study was on the optoelectronic properties of multilayered two-dimensional MoS2 and WS2 materials on a silicon substrate using sputtering physical vapor deposition (PVD) and chemical vapor deposition (CVD) techniques. For the first time, we report ultraviolet (UV) photoresponses under air, CO2, and O2 environments at different flow rates. The electrical Hall effect measurement showed the existence of MoS2 (n-type)/Si (p-type) and WS2 (P-type)/Si (p-type) heterojunctions with a higher sheet carrier concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The PD parameters such as responsivity, EQE, detetctivity, and photocurrent gain are important parameters to understand the Ir layer effect. The results of these factors are calculated under 0 V bias based on the previous studies [ 24,34 ] and reported in Figure a. It is important to mention here that all results are calculated at 0 V bias voltage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The PD parameters such as responsivity, EQE, detetctivity, and photocurrent gain are important parameters to understand the Ir layer effect. The results of these factors are calculated under 0 V bias based on the previous studies [ 24,34 ] and reported in Figure a. It is important to mention here that all results are calculated at 0 V bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previous study of depositing different samples at different temperatures, it was found that 200 °C was better for optoelectronic and electronic applications. [24] The process of creating an ultrathin layer of Ir, which is only a few nanometers thick, was completed using a Leica EM ACE600 US sputter coater. The layer was deposited onto a high vacuum film surface that had a condition of 1E3 mbar.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because a 5 V bias gave the sample more activations for better photoconductivity and a better photodetector response, we calculated the photocurrent gain, photoresponsivity ( ), external quantum efficiency (EQE), detectivity ( ), and finally the response/recovery time at 5 V biase. The calculations were collected based on the previous reports [ 54 , 55 , 56 ]. For a UV photodetector, the responsivity is important as it is a measure of the sensitivity of a photodetector to light.…”
Section: Optoelectronic Properties Of Moo 3 /Si Un...mentioning
confidence: 99%